An Approach for Assessing Large Online Communities in Informal Learning Environments - Silva, Rogério Ferreira da; Gimenes, Itana Maria de Souza; Maldonado, José Carlos (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
Online Learning Communities (OLC), supported by social web technologies, have proved to be beneficial for collaborative knowledge building, mainly in informal environments. There is an increasing interest in assessing online Social Learning (SL) in these communities. However, there is no agreement on how their performance can be measured. This paper presents an approach which combines structure and discourse analyses to assess large online communities used in SL. Its objective is to identify conditions and behavioral patterns associated to learning. The results point out a set of quantitative features which shows that participation and ongoing collaboration have a fundamental role for knowledge creation and sharing.